2011
DOI: 10.1002/jbm.b.31911
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular calcification in inducing fatigue and fracture of coronary stents

Abstract: Traditional approaches for in-vitro pulsatile and fatigue testing of endovascular stents do not take into consideration the pathologies of the stented vessel and their associated biomechanical effects. One important pathology is calcification, which may be capable of inducing changes in the vessel wall leading to inhomogeneous distribution of stresses combined with wall motion during the cardiac cycle. These local property changes in the region adjacent to stents could directly influence in-vivo stent performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 28 publications
(29 reference statements)
3
44
0
Order By: Relevance
“…For example, slip bands reported by Halwani et al. [1] at sites of stent fracture support the case for HCF as the probable fracture mechanism.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, slip bands reported by Halwani et al. [1] at sites of stent fracture support the case for HCF as the probable fracture mechanism.…”
Section: Introductionmentioning
confidence: 73%
“…[1][2][3]. Fractures were previously concealed by growth of neointima over stent struts and often went unnoticed as the tissue-growth provided support at the site of the fracture and provided coverage from the blood flow [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…in their detailed study, showed that the calcification of plaque increases the risk of stent fracture [32]. In addition, ostial [33] and bifurcation lesions [28] are reported as the predictors of stent fracture.…”
Section: Predictors and Mechanismsmentioning
confidence: 99%
“…Technical success and patency rates are reported to be lower in case of very calcified arteries [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it increases the occurrence of flow limiting dissections after PTA [8] and acute vessel recoil, with consequent increased use of stents. Also, in this condition calcium persists in playing an unfavourable role by increasing the risk of stent subexpansion, malposition, and fractures as shown in the coronary environment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%